1999
DOI: 10.1016/s0378-4274(99)00167-8
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of nitromusks in early lifestages of South African clawed frog (Xenopus laevis) and zebrafish (Danio rerio)

Abstract: Musk xylene (MX), musk ketone (MK) and musk moskene (MM) are synthetic nitro-containing fragrances. Due to their inherent lipophilicity and environmental persistence, they are frequently detected in environmental samples and especially in aquatic ecosystems. Despite this, the current environmental toxicity database of nitromusks is limited. Although nitromusks have been shown to accumulate in aquatic organisms, little is known about their potential developmental effects in the respective aquatic species. To in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Since MX was only found in 12% of the samples in low concentrations the risk of exposure to MX for the general population in Germany is estimated to be very low. Together with the low acute and chronic toxicity of MX in animal experiments (Christian et al 1999;Chou and Dietrich 1999) and the non-relevance to humans of MXinduced liver tumors in mice (Lehman-McKeeman and Caudill 1995;Lehman-McKeeman et al 1997a, 1997b, the toxic risk is also estimated to be very low. Decreased human risk is also probably true for other countries where the use of MX has been limited or banned.…”
Section: Resultsmentioning
confidence: 99%
“…Since MX was only found in 12% of the samples in low concentrations the risk of exposure to MX for the general population in Germany is estimated to be very low. Together with the low acute and chronic toxicity of MX in animal experiments (Christian et al 1999;Chou and Dietrich 1999) and the non-relevance to humans of MXinduced liver tumors in mice (Lehman-McKeeman and Caudill 1995;Lehman-McKeeman et al 1997a, 1997b, the toxic risk is also estimated to be very low. Decreased human risk is also probably true for other countries where the use of MX has been limited or banned.…”
Section: Resultsmentioning
confidence: 99%
“…The adverse impact of synthetic musk exposure to developing organisms has been reported (Rimkus and Wolf, ; Chou and Dietrich, ; Carlsson et al, ). Knockouts of polyisoprenylation pathway enzymes result in embryonic lethality, cardiomyopathy (Bergo et al, ) and extensive degeneration (Perez‐Sala, ; Tolmachova et al, ; Krishnan et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, contamination analysis of aquatic organisms revealed that in some cases, these metabolites were present at higher concentrations (mg/kg lipid) than their respective parent compounds (Rimkus et al, , 1999. All of the data presented so far demonstrate that nitromusks exert negligible acute toxicity on aquatic organisms even at the highest possible soluble concentrations tested (Tas and van de Plassche, 1996;Chou and Dietrich, 1999). However, no data are available regarding the potential endocrine modulating activity of these compounds and/or their metabolites in aquatic organisms.…”
Section: Introductionmentioning
confidence: 97%